Creación de la cafetería temática coffee book - Herrera Moreira, José (2010)
The following grade project look for measure the feasibility of introducing a new brand of Coffee Bar "Coffee- Book" in the Ecuadorian market, starting by Guayaquil city, through studies to know the people’s preferences, which would be our market goal. Coffee-Book will be a different proposal in comparison to the current coffees because it will offer a warm and friendly atmosphere that will resemble to a home’s living room, where the customers could get enjoy with a good book or simply have a usual friends’ talk accompanied by an excellent and delicious menu as if they were in the comfort of their homes. In addition to the usual services, Coffee-Book will also offers its installations for business purposes such as meeting that could be developed in an environment that combines the informality of a Coffee Bar and the flavor of a good cup of coffee with a high quality service.